Comparison of RDQ and GERDQ for Predicting Erosive Esophagitis in Patients with Typical GERD Symptoms - Titong Sugihartono; Amal Arifi Hidayat; Michael Austin Pradipta Lusida; Kuntaman; Hafeza Aftab; Muhammad Miftahussurur (The Korean Journal of Gastroenterology, 2023)
Background/Aims: The management decisions regarding gastroesophageal reflux disease (GERD) may differ according to the presence of erosive esophagitis. On the other hand, the availability of upper endoscopy in Indonesia is relatively limited. This study compared the Reflux Disease Questionnaire (RDQ) and the GERD questionnaire (GERDQ) performance in predicting the presence of clinically significant erosive esophagitis and determined the validity and reliability of the Indonesian-translated version of RDQ. Methods: Ninety-two adults with GERD suspicion were recruited. All patients completed RDQ and GERDQ. Receiver operating curve analysis was conducted on RDQ and GERDQ to evaluate their performance in discriminating LA GERD B or higher esophagitis from others. The translated RDQ preserved its main structure and was culturally adapted. Results: The patients were 66.3% female and 73.9% Javanese. Only 22 (23.9%) patients presented with LA grade B or higher erosive esophagitis. The RDQ showed a higher AUC than the GERDQ (0.602 vs. 0.589). A cutoff point of 20 was selected for the RDQ with sensitivity and specificity of 73% and 50%, respectively, whereas the optimal cutoff point of GERDQ was 8, with a sensitivity and specificity of 77% and 43%, respectively. The r-value greater than the critical value table (r>0.205, p<0.01) confirmed the construct validity of our translated RDQ. The questionnaire also demonstrated excellent reliability (α=0.900) and moderate similarity with the Indonesian version of GERDQ (κ=0.459, p<0.01). Conclusions: The RDQ is slightly superior to GERDQ in predicting the presence of clinically significant erosive esophagitis (LA grade B or higher). The Indonesian-translated RDQ is valid and reliable.